How Could Children’s Storybooks Promote Empathy? A Conceptual Framework Based on Developmental Psychology and Literary Theory - Kucirkova, Natalia (Frontiers in Psychology, 2019)
This conceptual paper proposes a framework for understanding the developmental mechanisms and literary characteristics that bind children’s storybooks with empathy. The article begins with a taxonomy of empathy composed of three key continuous dimensions: cognitive/emotional empathy, empathy for in-group and out-group members and empathy with positive and negative consequences. Insights from developmental psychology and literary theory form the basis for an interdisciplinary framework based on three premises: (1) book-reading can support empathy if it fosters in-group/out-group identification and minimizes in-group/out-group bias; (2) identification with characters who are dissimilar from the readers is the most valuable contribution of children’s storybooks to cognitive empathy; and (3) the quality of language positions children’s storybooks as an exceptional, but not exclusive, empathy-building form of fictional narratives. Implications for future intervention and empirical work are provided.